Greenleaf residences (Smart and sustainable single-storey terrace house in Kampar, Perak) - Mohd Sufian, Nurul Afiqa Farhani; Burhan, Nur Alia; Nor Azmi, Annas; Fitri, Ainur Fitriah Ainudin; Mohd, Thuraiya (2024)
Greenleaf Residences in Kampar, Perak is a new residential development that integrates smart and sustainable technologies in residential development. Its development combines cutting-edge technologies with sustainable practices to create eco-friendly, energy-efficient, and highly connected living spaces. These smart technologies require optimized resource consumption and sustainability is achieved through the use of renewable energy sources. This holistic approach not only minimizes the environmental footprint of the development, it also enhances the quality of life for the residents through increased comfort, safety, and convenience.